AGROLANCE: REPRESENTATION OF GROWTH BALANCE OF TOMATO PLANTS IN DRY LAND IN THE CONTEXT OF A DANCE WORK - Damanik, Desy Wulan Pita Sari; Alfassabiq Khairi (PT Inovasi Pratama Internasional, 2023)
Agrolance dance work is representation of research results entitled